Walk 6 CULTURE AND HISTORY - -, - (project baikal, 2011)
Irkutsk Cultural Center. Project Scientific and Technical Information Center Library Zagursky Music Theatre Palace for Civil Ceremonies Denis Matsuev’s Musical Studio and the Headquarters of the Festival “Stars at Baikal” Multilevel Universal Underground Space with Parking in the Historical Block 130 within The 3rd of July Street, Sedova Street and Kozhova Street in Irkutsk Multifunctional Building: Restaurant, Museum and Planetarium Center for Technical Creativity in Irkutsk Dwelling House , The 3rd of July Street 23 Dwelling House , The 3rd of July Street 21 Dwelling House Transferred from Gavrilova Street 3 Dwelling House , The 3rd of July Street 19A